2018
DOI: 10.1177/1055665618765829
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Innovative Multidisciplinary Management of Hallermann-Streiff Syndrome

Abstract: Hallermann-Streiff syndrome (HSS) is a rare congenital disorder that mainly affects head and face development. We described the different patterns of the disease throughout the whole growth period and provided innovative treatment steps. Indeed, early genioplasty and dental implantation before growth completion were performed. These steps allowed to improve facial growth and to provide orthodontic anchorage, respectively. Complementary orthognathic surgery achieved satisfactory occlusion and refined aesthetics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In this case, the most remarkable dental anomaly was oligodontia characterized by many missing teeth (n≥6). The patient's permanent teeth (except for 16,17,26,27,36,37,46,47,13,23) have been detected missing congenitally by panoramic radiograph. However, it has been suggested that the age of 10 years was critical for confirming the absence of a second premolar (15).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In this case, the most remarkable dental anomaly was oligodontia characterized by many missing teeth (n≥6). The patient's permanent teeth (except for 16,17,26,27,36,37,46,47,13,23) have been detected missing congenitally by panoramic radiograph. However, it has been suggested that the age of 10 years was critical for confirming the absence of a second premolar (15).…”
Section: Discussionmentioning
confidence: 95%
“…The incidence of dental anomalies, one of these criteria, was 85% (12). These were mandibular hypoplasia, hypodontia, malocclusion, dental malformation, natal teeth and premature eruption in primary dentition (13). Odontodysplasia (6,14), permanent teeth with the absence of roots, impacted teeth (10), hypoplastic coronoid, and condylar processes (4) were also reported in patients with HSS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…52 Dong et al reported porous boron-containing covalent organic frameworks, which exhibit strong ion adsorption ability and served as competent additives for Li + ion transference number improvement of the polymer electrolyte. 53 In recent times, Zhang's group prepared and immobilized Boron-based COF onto the surface of a capillary (COF-1@capillary column) and showed its application towards electro chromatographic separation [Fig. 3a].…”
Section: Covalent Organic Frameworkmentioning
confidence: 99%
“…Maxillary hypoplasia and malocclusion are frequently reported (Parikh & Gupta, ). Dental anomalies are a common finding and may include absence of teeth, premature eruption and persistence of deciduous teeth, missing of multiple permanent teeth, malocclusion and open bite, malformed teeth, severe and premature caries, and especially natal and/or neonatal teeth (Abadi, Van Sickels, McConnell, & Kluemper, ; Dulong et al, ; Hutchinson, ; Sharp & Kopel, ). An optimal oral hygiene is of particular importance for patients with HSS and often they need a multidisciplinary approach to manage the orofacial abnormalities.…”
Section: Clinical Features Of Hallermann–streiff Syndromementioning
confidence: 99%